Mitigation-Based Enlightenment Da'wah (Social Movement of MDMC Sulawesi-Southeast in Psychological Assistance to COVID-19 Survivors) - Muhammad Alifuddin; Moh. Toriqul Chaer; Sukatin Sukatin (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to describe the mitigation-based MDMC enlightenment da'wah in handling the impact of the pandemic, especially providing psychological assistance to the COVID-19 survivors' community. Research data were obtained through in-depth interviews, observation, and document review. All data obtained were analyzed using the Miles and Huberman paradigm. The results showed that Muhammadiyah first carried out mitigation-based enlightenment da'wah through various social activities by providing public awareness in dealing with the COVID-19 pandemic. Second, da'wah based on a mitigation approach was carried out by the Southeast Sulawesi MDMC, with three approaches, an oral approach, brochures, and social media. The bil hal or bi al-amal approach was carried out through measured and planned actions, such as spraying disinfectants, distributing masks, sharing food, and providing scholarships to survivors. Third, the enlightenment da'wah based on the mitigation movement conducted by MDMC was inclusive and universally humanitarian oriented. This activity has proven to improve the psychological condition of the COVID-19 survivors. The pandemic period requires physical distancing, but social attachment must be solid because caring for each other can reduce stress levels and make the body's immune stronger.